El aftermath de la victoria de David ante Goliat: A propósito de la ejecución de laudos en los arbitrajes entre inversor-Estado - Bedoya Denegri, Alonso (2023)
It is well known that the confrontation in an arbitral procedure to obtain a favorable award implies a strenuous effort by both the parties and their respective legal. Even more in the framework of international arbitration and investment treaty arbitration between a State and a foreign investor. However, it should not be overlooked that many times the heart of the matter lies in the enforcement of the award. Having a favorable award is no small task, yet we cannot ignore the dire reality in which investors face off a perilous journey in order to enforce what is lawfully theirs. Thus, this article deals with the aftermath of a victorious award for the foreign investor, who often cannot see the decision contained in the award materialize, due to a lack of compromise of the respective State which adduces several foreign immunity regulations, which makes enforcing an award a titanic feat, therefore turning the arbitral victory into a Pyrrhic victory. In this scenario, and for illustration purposes we will use, the biblical passage of David and Goliath to demonstrate the Dantesque feat to which each investor must succumb in order to enforce assets pertaining to the State. Consequently, this paper will analyze the ways in which investors may have a chance of enforcing a favorable award without being limited to sovereign immunity legislation.